Tetracycline electrochemical sensor based on nanocomposite and detection method
An electrochemical sensor that constructs a three-dimensional porous silver nanolayer on the surface of an ITO electrode solves the problems of complexity and high cost of existing detection methods, and achieves high-sensitivity and low-cost tetracycline detection, which is suitable for rapid detection in the environment and food.
Patent Information
- Application Number
- CN202511238665.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2026-01-09
AI Technical Summary
Existing methods for tetracycline detection, such as high-performance liquid chromatography and mass spectrometry, suffer from problems such as expensive instruments and complex operation. Furthermore, tetracycline is difficult to degrade by microorganisms in the environment, leading to health and ecological risks. Therefore, there is a need to develop efficient and accurate detection technologies.
An electrochemical sensor based on silver nanoparticle-modified indium tin oxide nanocomposite material (AgNPs/ITO) was constructed. A three-dimensional porous silver nanolayer was built on the surface of the ITO electrode by electrodeposition to increase the electrochemical active area. Rapid detection was achieved by utilizing the surface plasmon resonance effect of AgNPs and the synergistic effect of π-π stacking between tetracycline molecules.
It achieves high sensitivity and low cost tetracycline detection with a detection limit of 3.2 μmol/L, and is suitable for the detection of tetracycline residues in environmental water and food. It has good selectivity and rapid response capability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental analysis and detection technology, specifically a tetracycline electrochemical sensor and detection method based on nanocomposite materials. Background Technology
[0002] Tetracycline (TC), a broad-spectrum antibiotic, is widely used in human medicine, animal husbandry, and aquaculture due to its low cost and high antibacterial activity; it is even excessively added as a growth promoter. However, the abuse of TC has led to increasingly serious problems with its residues in the food chain and aquatic environments. Studies have shown that TC is difficult for microorganisms to degrade in the natural environment and accumulates in the human body through drinking water or the food chain over a long period, potentially inducing health risks such as intestinal flora imbalance, diarrhea, and oral diseases. Simultaneously, its ecotoxicity may disrupt aquatic biological communities and threaten ecological balance. Therefore, developing efficient and accurate TC residue detection technologies is of great significance for safeguarding public health and environmental safety.
[0003] Existing detection methods such as high-performance liquid chromatography (HPLC) and mass spectrometry (MS), while highly sensitive, suffer from drawbacks such as expensive instruments and complex operation. Electrochemical sensors have become a research hotspot due to their advantages of speed, low cost, and ease of miniaturization. Furthermore, the introduction of nanomaterials further enhances sensing performance; among them, silver nanoparticles exhibit surface plasmon resonance, which can enhance electron transfer efficiency, enabling signal amplification and specific recognition. This invention studies the rapid determination of tetracycline in water using electrodeposited silver nanoparticles on an ITO electrode, successfully constructing an electrochemical sensor based on silver nanoparticle-modified indium tin oxide nanocomposite material (AgNPs / ITO) for determining TC residues in water. Summary of the Invention
[0004] To address the above problems, this invention provides a tetracycline electrochemical sensor and detection method based on nanocomposite materials. This sensor has high sensitivity, good selectivity and low cost, and can be used for rapid detection of tetracycline antibiotics in environmental water and food.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A tetracycline electrochemical sensor based on nanocomposite materials includes a silver nanoparticle-modified ITO electrode, a reference electrode, and a counter electrode, wherein the silver nanoparticle-modified ITO electrode is constructed on the ITO surface using an electrostatic deposition method to form a three-dimensional porous silver nanoparticle layer.
[0006] In a preferred embodiment, the method for preparing the nano-silver modified ITO electrode includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned in ammonia water, anhydrous ethanol and ultrapure water in sequence, and then APTMS solution was added for further soaking. The glass was then rinsed clean with ultrapure water. (2) Prepare silver nitrate solution and potassium nitrate solution, mix them in an electrolytic cell in proportion, deposit under constant voltage, rinse with ultrapure water and dry under infrared lamp; (3) Apply Nafion solution evenly to the dry surface of the modified electrode and allow it to dry at room temperature.
[0007] In a preferred embodiment, the ammonia concentration in the steps is 20%, the ultrasonic cleaning is performed for 10-15 minutes, the APTMS solution is added at 1% of the total solution volume, and the soaking time is 3-4 hours.
[0008] In a preferred embodiment, the concentration of the silver nitrate solution prepared in the above steps is 10 mmol / L, the concentration of the potassium nitrate solution is 0.1 mol / L, and the mixing ratio is 2:1.
[0009] In a preferred embodiment, the constant voltage deposition voltage is -0.1 to -0.3V, and the deposition time is 50 to 80 seconds.
[0010] In a preferred embodiment, the Nafion solution concentration in the above steps is 0.5 wt%, the amount used is 5 μL, and the drying time is 12-14 h.
[0011] A detection method for tetracycline based on a nanocomposite material electrochemical sensor includes the following steps: (1) Incubate the electrochemical sensor in a solution containing tetracycline antibiotics; (2) A three-electrode system was used to perform cyclic voltammetry or linear sweep voltammetry in a citric acid-sodium citrate buffer solution with a pH of 3.0-4.5; (3) Calculate the concentration of tetracycline antibiotics based on the test results.
[0012] In a preferred embodiment, the potential scan range of the cyclic voltammetry is 0.3-0.8V, the scan rate is 50mV / s, and the oxidation peak value is recorded.
[0013] In a preferred embodiment, the potential scanning range of the linear scanning voltammetry is 0.3-0.7V, the scanning speed is 50mV / s, and the oxidation peak value is recorded.
[0014] In a preferred embodiment, the three-electrode system uses a nano-silver modified ITO electrode (AgNPs / ITO) as the working electrode, an Ag / AgCl (saturated KCl solution) electrode as the reference electrode, and a platinum wire electrode as the counter electrode.
[0015] Compared with existing technologies, the beneficial effects of this invention are as follows: This invention constructs a three-dimensional porous silver nanolayer on the ITO surface through electrodeposition, increasing the electrochemically active area and promoting the electron transfer rate. Utilizing the synergistic effect of AgNP surface plasmon resonance and the π-π stacking between tetracycline molecules, the detection sensitivity is improved. In a citrate-sodium citrate buffer at pH=3, with a scan rate of 50 mV / s, it exhibits a good linear relationship in the concentration range of 30-110 μmol / L, with a detection limit of 3.2 μmol / L, providing an efficient and reliable analytical method for the detection of antibiotic residues in environmental water bodies. Attached Figure Description
[0016] Figure 1 This is a scanning electron microscope image of the electrode of the present invention, wherein... Figure 1 (a) is a SEM image of the bare ITO electrode. Figure 1 (b) is a SEM image of the AgNPs / ITO electrode; Figure 2 EDS characterization image of the AgNPs / ITO electrode prepared in Example 1; Figure 3 The image shows the cyclic voltammetry scan results for Example 2, where the red line represents the CV curve of the bare ITO electrode sensor in tetracycline, and the black line represents the CV curve of the AgNPs / ITO electrode sensor in tetracycline. Figure 4 The image shows the LSV diagram of the AgNPs / ITO electrode in Example 3, where... Figure 4 (a) is the LSV curve of TC at different concentrations, where the black line represents 30 μmol / L, the red line represents 50 μmol / L, the blue line represents 70 μmol / L, the green line represents 90 μmol / L, and the purple line represents 110 μmol / L; Figure 4 (b) is a graph showing the linear relationship between peak current and concentration; Figure 5 The image shows the LSV diagram of the AgNPs / ITO electrode in Example 4, where... Figure 5 (a) is the LSV curve of TC at different scan rates, where the black line represents 10 mV / s, the red line represents 20 mV / s, the blue line represents 30 mV / s, the green line represents 40 mV / s, and the purple line represents 50 mV / s; Figure 5 (b) is a graph showing the linear relationship between peak current and scanning speed; Figure 6 The peak current of 90 μmol / L TC in buffer solutions at different pH values was measured using the AgNPs / ITO electrode in Example 5, showing the relationship between pH and the pH value. Detailed Implementation
[0017] To enable those skilled in the art to better understand the technical solution, the present invention will be described in detail below with reference to embodiments. The description in this part is only exemplary and explanatory, and should not be used to limit the scope of protection of the present invention in any way.
[0018] The information on the materials and reagents used in the following examples is as follows: ITO conductive glass: purchased from Shenzhen Lanjingling Information Technology Co., Ltd. 7-10Ω.
[0019] APTMS (3-aminopropyltrimethoxysilane, Röhn's reagent): concentration 97%.
[0020] Example 1: The preparation method of the nano-silver modified ITO electrode includes the following steps: (1) Place the ITO conductive glass in 20% ammonia water, anhydrous ethanol and ultrapure water in sequence for ultrasonic cleaning for 10-15 minutes, then add 1% APTMS solution and continue soaking for 3-4 hours, and rinse with ultrapure water. (2) Prepare 10 mmol / L silver nitrate solution and 0.1 mol / L potassium nitrate solution, mix them in an electrolytic cell at a ratio of 2:1, deposit at a constant voltage of 0.3V for 60s, rinse with ultrapure water and dry under an infrared lamp; (3) 5 μL of 0.5 wt% Nafion solution was uniformly dropped onto the dry modified electrode surface and dried at room temperature for 12-14 h.
[0021] The surface morphology of bare ITO (i.e., unmodified ITO electrode) and the AgNPs / ITO electrode prepared in Example 1 were systematically characterized using scanning electron microscopy (SEM). Figure 1 The SEM image in (a) shows that its surface exhibits a typical smooth planar structure with clear grain boundary contours and uniform distribution of conductive particles, indicating that the ITO substrate possesses excellent crystallinity and conductivity stability. After constant current deposition modification, the AgNPs / ITO electrode (such as...) Figure 1 (b) The surface morphology changes significantly: high-density silver nanoparticles (AgNPs) are uniformly attached to the ITO substrate in a three-dimensional porous structure. Abundant pore channels are formed between the silver nanoparticles. This hierarchical porous structure not only increases the specific surface area of the electrode, but also provides more adsorption sites for tetracycline molecules. At the same time, it optimizes the interfacial electron transfer path, thereby significantly improving the catalytic activity and electron transfer efficiency of the electrode and exhibiting high conductivity.
[0022] Further elemental distribution characterization of the AgNPs / ITO electrode was performed using energy dispersive spectroscopy (EDS). Figure 2The results showed that Ag elements exhibited a highly uniform dispersion on the ITO surface, confirming that electrodeposition could regulate the nucleation and growth process of silver nanoparticles. Combined with SEM and EDS results, it was found that the porous network structure and uniform distribution characteristics of AgNPs synergistically promoted electrolyte penetration through capillary action in the three-dimensional porous structure, shortening the ion diffusion path, and the plasmon resonance effect of high-density AgNPs enhanced the local electric field intensity on the electrode surface, thereby amplifying the electrochemical response signal.
[0023] Example 2: A detection method for tetracycline based on a nanocomposite material electrochemical sensor, comprising the following steps: The electrochemical sensor was incubated in a solution containing 70 μmol / L tetracycline antibiotics; A three-electrode system was used, with a nano-silver modified ITO electrode (AgNPs / ITO) as the working electrode, an Ag / AgCl (saturated KCl solution) electrode as the reference electrode, and a platinum wire electrode as the counter electrode. Cyclic voltammetry was performed in a citrate-sodium citrate buffer solution at pH 4.0. The experimental results are as follows: Figure 3 As shown.
[0024] Figure 3 The results showed that the bare ITO electrode did not exhibit significant redox peaks in the 0.3–0.8 V potential range, indicating that TC molecules have difficulty undergoing effective electron transfer on the unmodified electrode surface. In contrast, the AgNPs / ITO electrode showed a significant oxidation peak at 0.572 V. This phenomenon is attributed to the oxidation activity of the phenolic hydroxyl (-OH) and carbonyl (C=O) functional groups in the TC molecule. Under the catalysis of AgNPs, the TC molecule undergoes a deprotonation reaction at the electrode interface through an adsorption-oxidation mechanism, generating an electroactive quinone structure, thereby producing a detectable oxidation current signal. The experiment demonstrates that the silver nanoparticles have good catalytic properties for tetracycline, amplifying the electrochemical signal, and the current generated by the oxidation reaction of tetracycline molecules is recorded.
[0025] Example 3: This example uses linear sweep voltammetry (LSV) to investigate the quantitative and qualitative analysis of tetracycline using an AgNPs / ITO electrode, examining the linear range of tetracycline (TC) on the AgNPs / ITO electrode. Figure 4As shown, when the concentration of tetracycline was gradually increased from 30 μmol / L to 110 μmol / L, the oxidation peak current increased with increasing concentration, showing a good linear relationship with concentration. The linear regression equation was Ip(mA) = 0.132 + 0.0187x(μmol / L), with a correlation coefficient R² = 0.98, indicating that the electrode has excellent quantitative analysis capability over a wide concentration range. The limit of detection (LOD) was calculated to be 3.2 μmol / L using the signal-to-noise ratio method (S / N = 3). Compared with similar electrochemical sensors (Table 1), the LOD is similar, indicating that the AgNPs / ITO electrode has excellent sensitivity and detection capability for tetracycline.
[0026] Table 1 Comparison of TC electrochemical sensors
[0027] Example 4: This example investigates the electron transfer mechanism of tetracycline (TC) at the AgNPs / ITO electrode interface. The effect of the scan rate (10–50 mV / s) on the oxidation peak current of 90 μmol / L TC was studied using a linear sweep voltammetry (LSV) system. Figure 5 (As shown). Experimental results show that as the scan rate (v) increases from 10 mV / s to 50 mV / s, the oxidation peak current (Ip) linearly increases from 0.83 mA to 1.828 mA. The oxidation peak current (Ip) exhibits a good linear relationship with the scan rate (v), with a linear regression equation of Ip(mA) = 0.4665 + 0.027v(mV / s) (R² = 0.92), and a slight shift in peak potential occurs. This is consistent with the typical characteristics of adsorption-controlled electrochemical reactions. This phenomenon indicates that the oxidation reaction rate of TC molecules on the AgNPs / ITO electrode surface is limited by its adsorption-desorption process, rather than the diffusion mass transfer step in solution. The Ip of adsorption-controlled reactions should be proportional to the scan rate v, while the diffusion-controlled reactions are linearly correlated with v¹ / ². The strong correlation of Ip∝v in this example confirms the adsorption-dominated kinetic process. This characteristic stems from the three-dimensional porous structure of the AgNPs / ITO electrode, whose abundant active sites efficiently capture TC molecules through π-π interactions and hydrogen bond networks, forming a stable adsorption layer. Based on these results, 50 mV / s was selected as the optimized scan rate.
[0028] Example 5: This example aims to investigate the effects of buffer solution type and pH value on the electrochemical response, such as the effect of citrate-sodium citrate and PBS (pH=7) on the TC peak current. The results are as follows... Figure 6 As shown, the results indicate that TC exhibits a significant electrochemical reaction in a citrate-sodium citrate buffer solution, which is attributed to the citrate anion (Citrate-sodium citrate-C ... 3-The dual effects of PO42- (as opposed to TC) include stabilizing the AgNPs surface through coordination to prevent nanoparticle aggregation, and adjusting the ionic strength of the solution to optimize the electric double layer structure, promoting the directional adsorption of TC molecules at the electrode interface. In contrast, the high concentration of PO42- in PBS... 3- It may compete with TC for adsorption sites, leading to signal suppression. Therefore, citrate-sodium citrate was chosen as the electrolyte solution, and the effect of the pH value (2.5-4.5) of the citrate-sodium citrate buffer on the detection sensitivity was further investigated. Linear sweep voltammetry was used to detect 90 μmol / L tetracycline using AgNPs / ITO. Figure 5 As shown, the TC peak current gradually increases from pH=2.5 (Ip=1.529 mA), reaching a maximum value of Ip=3.111 mA at pH=4.0, and then begins to decrease. Therefore, pH=4.0 is the optimal pH for TC detection.
[0029] Example 6: This example was designed to verify the selectivity of the AgNPs / ITO sensor for tetracycline (TC) detection. In a citrate-sodium citrate buffer solution (pH=4.0) containing 90 μmol / L TC, 10 times the concentration (900 μmol / L) of Ca2+ was added. 2+ Mg 2+ and NH4 + The interference rate was calculated through three independent repeated experiments, and the results showed that Ca 2+ Mg 2+ and NH4 + The interference rates were -1.5%, 0.13%, and -0.17%, respectively, all well below the ±5% threshold. This result indicates that even under conditions of high concentrations of coexisting ions, the sensor can still maintain its specific recognition ability for TC, with minimal interference to the TC detection results.
[0030] It should be noted that, in this document, the terms "comprising," "including," and any other variations are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Specific examples have been used in this document to illustrate the principles and implementation methods of the present invention. These examples are merely for the purpose of helping to understand the method and core ideas of the present invention. The above descriptions are only preferred embodiments of the present invention. It should be pointed out that, due to the limitations of written expression and the objective existence of infinite specific structures, those skilled in the art can make several improvements, modifications, or variations without departing from the principles of the present invention, and can also combine the above technical features in an appropriate manner. These improvements, modifications, variations, or combinations, or the direct application of the concept and technical solution of the present invention to other situations without modification, should all be considered within the scope of protection of the present invention.
Claims
1. A tetracycline electrochemical sensor based on nanocomposite materials, characterized in that, The sensor includes a silver nanoparticle-modified ITO electrode, a reference electrode, and a counter electrode. The silver nanoparticle-modified ITO electrode is constructed by electrostatic deposition of a three-dimensional porous silver nanoparticle layer on the ITO surface.
2. The tetracycline electrochemical sensor based on nanocomposite materials according to claim 1, characterized in that, The preparation method of the nano-silver modified ITO electrode includes the following steps: (1) The ITO conductive glass was ultrasonically cleaned in ammonia water, anhydrous ethanol and ultrapure water in sequence, and then APTMS solution was added for further soaking. The glass was then rinsed clean with ultrapure water. (2) Prepare silver nitrate solution and potassium nitrate solution, mix them in an electrolytic cell in proportion, deposit under constant voltage, rinse with ultrapure water and dry under infrared lamp; (3) Apply Nafion solution evenly to the dry surface of the modified electrode and allow it to dry at room temperature.
3. The tetracycline electrochemical sensor based on nanocomposite materials according to claim 2, characterized in that, In step (1), the ammonia concentration is 20%, ultrasonic cleaning is performed for 10-15 minutes, the amount of APTMS solution added is 1% of the total volume of the solution, and the soaking time is 3-4 hours.
4. The tetracycline electrochemical sensor based on nanocomposite materials according to claim 2, characterized in that, In step (2), the concentration of the silver nitrate solution prepared is 10 mmol / L, the concentration of the potassium nitrate solution is 0.1 mol / L, and the mixing ratio is 2:
1.
5. A tetracycline electrochemical sensor based on nanocomposite materials according to claim 2, characterized in that, The constant voltage deposition voltage is -0.1 to 0.3V, and the deposition time is 50 to 80 seconds.
6. The tetracycline electrochemical sensor based on nanocomposite materials according to claim 2, characterized in that, In step (3), the Nafion solution concentration is 0.5wt%, the amount used is 5μL, and the solution is dried for 12-14 h.
7. A detection method for tetracycline based on a nanocomposite material electrochemical sensor as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) Incubate the electrochemical sensor in a solution containing tetracycline antibiotics; (2) A three-electrode system was used to perform cyclic voltammetry or linear sweep voltammetry in a citric acid-sodium citrate buffer solution with a pH of 3.0-4.5; (3) Calculate the concentration of tetracycline antibiotics based on the test results.
8. The tetracycline electrochemical sensor based on nanocomposite materials according to claim 7, characterized in that, The cyclic voltammetry method has a potential scan range of 0.3-0.8V and a scan rate of 50mV / s, and records the oxidation peak value.
9. A tetracycline electrochemical sensor based on nanocomposite materials according to claim 7, characterized in that, The linear scanning voltammetry method described herein has a potential scanning range of 0.3-0.7V and a scanning speed of 50mV / s, and records the oxidation peak value.
10. A tetracycline electrochemical sensor based on nanocomposite materials according to claim 7, characterized in that, The three-electrode system uses a nano-silver modified ITO electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum wire electrode as the counter electrode.